Incidence and survival of hematological cancers among adults ages ≥75 years. (13th April 2018) - Krok‐Schoen, Jessica L.; Fisher, James L.; Stephens, Julie A.; Mims, Alice; Ayyappan, Sabarish; Woyach, Jennifer A.; Rosko, Ashley E.
Abstract: Evaluating population‐based data of hematologic malignancies (HMs) in older adults provides prognostic information for this growing demographic. Incidence rates and one‐ and five‐year relative survival rates were examined for specific HMs among adults ages ≥75 years using data from the Surveillance, Epidemiology and End Results (SEER) Program. Hematologic malignancy cases (Hodgkin lymphoma (HL), non‐Hodgkin lymphoma (NHL), multiple myeloma (MM), acute lymphocytic leukemia (ALL), chronic lymphocytic leukemia (CLL), acute myeloid leukemia (AML), and chronic myeloid leukemia (CML)) were reported to one of 18 SEER registries. Recent average annual (2010–2014) incidence rates and incidence trends from 1973 to 2014 were examined for cases ages ≥75 years. One‐ and five‐year relative cancer survival rates were examined for adults ages ≥75 years diagnosed 2007–2013, with follow‐up into 2014. From 1973 to 2014, incidence rates increased for NHL, MM, and AML, decreased for HL, and remained relatively stable for ALL, CLL, and CML among adults ages ≥75 years. The highest one‐ and five‐year relative survival rates were observed among adults with CLL ages 75–84 years (1 year: 91.8% (95% CI = 91.8–90.8)) and 5 years: 76.5% (95% CI = 74.2–78.6)). The lowest one‐ and five‐year survival rates were observed among adults with AML ages 75–84 (1 year: 18.2% (95% CI = 74.2–78.6) and 5 years: 2.7% (95% CI = 2.0–3.6)). Survival for older adults ages ≥75 years with HMs is poor, particularly for acute leukemia. Understanding the heterogeneity in HM outcomes among older patients may help clinicians better address the hematological cancer burden and mortality in the aging population. Abstract : Incidence rates and one‐ and five‐year relative survival rates were examined for specific HMs among adults ages ≥75 years using data from the Surveillance, Epidemiology, and End Results (SEER) Program. From 1973 to 2014, incidence rates increased for NHL, MM, and AML, decreased for HL, and remained relatively stable for ALL, CLL, and CML among adults ages ≥75 years. Survival for older adults ages ≥75 years with HMs is poor, particularly for acute leukemia.